Categories and functions of imperative sentences in the Film Calamity: A study of French-language film dialogue - Oktavian, Rully Ahmad Fauzi; Mutiarsih, Yuliarti; Karimah, Iim Siti (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2026)
The use of imperative sentences in film dialogues not only represents grammatical structures, but also reflects social relations, power dynamics, and character construction, so that a study is needed that can explain the variations in the forms and functions of imperatives contextually. This study aims to identify, classify, and describe the categories and functions of imperative sentences in the dialogues of the French film Calamity, une enfance de Martha Jane Cannary based on Zhang's classification of strong, neutral, and weak tones. This study used a qualitative descriptive approach with observation, documentation, and interview techniques to support data interpretation. The data sources are all imperative sentences contained in the film dialogues, which are then classified and analyzed based on the distribution of tone categories and their communicative functions. The results show that strong-toned imperatives dominate and function primarily to command, reprimand, and give instructions in the context of situations that require assertiveness and quick responses. Neutral and weak-toned imperatives appear in the functions of giving advice, reminding, requesting, and pleading, which reflect a more cooperative and emotional interpersonal dynamic. In conclusion, the classification of imperative tones has proven effective in explaining the relationship between syntactic structure and pragmatic function in the film medium, and shows that imperative sentences play a role as a discursive strategy in building social relations and character identities in audiovisual narratives.